Genetic Associations of ACOX2 Gene with Milk Yield and Composition Traits in Chinese Holstein Cows - Hui Cao; Zhe Wang; Lingna Xu; Bo Han; Dongxiao Sun (Animals)
In our previous studies on the liver proteome of Holstein cows, the acyl-CoA oxidase 2 (ACOX2) gene was identified as a promising candidate for milk traits, being involved in the processes of fatty acid metabolism and bile acid formation. Herein, we evaluated its genetic effects on milk production traits in 922 Chinese Holstein cows. By sequencing the entire coding region and 2000 bp of the 5′ and 3′ flanking sequences of the ACOX2 gene, we identified a total of five SNPs, including one SNP in the 5′ UTR, one in intron 5, and three in the 3′ flanking region. Using an animal model, we found that the SNPs rs109066086, rs109665171, and rs454339362 were significantly associated with at least one of the milk production traits, including 305-day milk yield, milk fat yield, milk protein yield, milk fat percentage, and milk protein percentage in the first lactation (p ≤ 4.03 × 10−2). And in the second lactation, all five SNPs were significantly associated with at least three of the milk production traits (p ≤ 1.17 × 10−2). We also found that in the second lactation, the SNP rs209677248 had a high phenotypic variance rate for milk protein percentage, with a value of 4.90%. With Haploview 4.2, it was observed that the four SNPs formed two haplotype blocks, which were significantly associated with the 305-day milk, fat, and protein yields (p ≤ 1.03 × 10−2; p ≤ 8.60 × 10−3; p ≤ 3.20 × 10−3). In addition, it was predicted that the T allele in the SNP rs109066086 created TFBSs for transcription factors NC2R2 and TFAP4, thereby potentially affecting ACOX2 expression. Overall, our results provide the first confirmation of the genetic effects of the ACOX2 gene on milk yield and composition traits in dairy cattle and revealed the referable molecular markers for genomic selection.